Strategies Implemented by Islamic Religious Education Teachers in Developing Religious Tolerance among Students at Ndona 1 State Junior High School, Ende Regency - Nadya Muktar; Erlan Muliadi; Erwin Padli (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the strategies employed by Islamic Religious Education (PAI) teachers to foster religious tolerance at SMP Negeri 1 Ndona, Ende Regency, while identifying the supporting and inhibiting factors of implementation. A qualitative phenomenological method was applied to gain deep understanding of participants’ experiences and perspectives. Data were collected through observation, interviews, and documentation involving PAI teachers, the school principal, Catholic religious education teachers, Muslim and non-Muslim students. Data analysis followed the interactive model of Saldanak (2014) through data reduction, data presentation, and conclusion drawing, with source and methodological triangulation to ensure validity. Results indicate that PAI teachers employ three key strategies: (1) integrating tolerance values into formal instruction through dialogic and contextual learning, (2) serving as role models by demonstrating inclusive conduct in daily school interactions, and (3) providing personal guidance outside class hours to address students’ social attitudes. Supporting factors include adequate facilities and inclusive school policies, while inhibiting factors include students’ exclusive home environments and limited understanding of religious diversity. This study concludes that the cultivation of religious tolerance requires a holistic, integrated approach combining instructional strategies, exemplary modeling, and sustained personal guidance, and that long-term effectiveness depends on consistent collaboration among schools, families, and the broader community. These findings contribute to the development of PAI-based tolerance education models applicable in religiously diverse public school contexts.